A Systematic and Evidence-Based Approach to the Management of Vertebral Metastasis. (2nd August 2011) - Jennelle, Richard L. S.; Vijayakumar, Vani; Vijayakumar, Srinivasan
Abstract : Diagnosis and management of vertebral metastasis requires a systematic approach to patient identification as well as selection of appropriate therapy. Rapid identification and prompt intervention in the treatment of malignant epidural spinal cord compression (MESCC) is key to maintaining quality of life. This paper provides a series of tools as well as guidance in selecting effective and evidence-based therapy individualized to the specific patient.